Pre-Diagnostic Carbohydrate Intake and Treatment Failure After Radical Prostatectomy for Early-Stage Prostate Cancer - Kim, Kyeezu (Cancer Causes Control, 2019)
PURPOSE: An association between dietary carbohydrate intake and prostate cancer (PCa) prognosis is biologically plausible, but data are scarce. This prospective cohort study examined the relation between pre-diagnostic carbohydrate intake and treatment failure following radical prostatectomy for clinically early-stage PCa. METHODS: We identified 205 men awaiting radical prostatectomy and assessed their usual dietary intake of carbohydrates using the 110-item Block food frequency questionnaire. We also evaluated carbohydrate intake quality using a score based on the consumption of sugars relative to fiber, fat, and protein. Logistic regression analyzed their associations with the odds of treatment failure, defined as a detectable and rising serum prostate-specific antigen (PSA) or receiving androgen deprivation therapy (ADT) within 2 years. RESULTS: Sucrose consumption was associated with a higher odds and fiber consumption with a lower odds of ADT after accounting for age, race/ethnicity, body mass index, and tumor characteristics (odds ratio [OR] (95% confidence interval [CI]) = 5.68 (1.71, 18.9) for 3rd vs. 1st sucrose tertile and 0.88 (0.81, 0.96) per gram of fiber/day, respectively). Increasing carbohydrate intake quality also associated with a lower odds of ADT (OR (95%CI) = 0.78 (0.66, 0.92) per unit increase in score, range = 0 to 12). CONCLUSIONS: Pre-diagnostic dietary carbohydrate intake composition and quality influence the risk of primary treatment failure for early-stage PCa. Future studies incorporating molecular aspects of carbohydrate metabolism could clarify possible underlying mechanisms.